Flu, Floods, and Fire: Ethical Public Health Preparedness - Phelan, Alexandra L. (The Hastings Center report, 2017)
Even as public health ethics was developing as a field, major incidents such as 9/11 and the SARS epidemic propelled discourse around public health emergency preparedness and response. Policy and practice shifted to a multidisciplinary approach, recognizing the broad range of potential threats to public health, including biological, physical, radiological, and chemical threats. This propelled the development of surveillance systems to detect incidents, laboratory capacities to rapidly test for potential threats, and therapeutic and social countermeasures to prepare for and respond to a range of hazards. In bringing public health ethics and emergency preparedness together, Emergency Ethics: Public Health Preparedness and Response adds depth and complexity to both fields. As global threats continue to emerge, the book, edited by Bruce Jennings, John D. Arras, Drue H. Barrett, and Barbara A. Ellis, will offer a vital compass.